Influence of interspecies interactions on biomass and extracellular polymeric substances of bacterial biofilms - Mercedes Baltazara Schettini Alava; Naga Raju Maddela (Universa Medicina, 2023)
BackgroundStudies with emphasis on pure and mixed-species biofilms are of significant importance in understanding biofilm formation mechanisms during microbial infections. This research aims to evaluate pure- and dual-species biofilms of Escherichia coli (code A), Staphylococcus aureus (code B), Klebsiella pneumoniae (code C) and Pseudomonas aeruginosa (code D) pathogenic bacterial species and their production of biofilm exopolysaccharides at laboratory scale. MethodsBiofilm biomass (A595) of pure- and dual-species cultures was determined by means of a microtiter plate assay in triplicate using a microplate photometer (Fisher Scientific, type-357). Extracellular polymeric substances (EPS) and soluble microbial products (SMP) were extracted from the biofilm cells (pure- and dual-species cultures) using the alkaline-heat extraction method. Dry weights (g/L) of EPS and SMP were determined by drying the samples at 105 °C for 8 hours. ResultsKlebsiella pneumoniae biofilm biomass accounted for a 28-72% greater biofilm biomass than the other bacteria. Experimental values of dual-species biofilm biomasses were in the range of 6% to 30% over theoretical values. The experimental value of one dual-species (bacteria B + D) biofilm biomass was 30% higher than its expected value. Decrease or increase in the dual-species biofilm biomass of either bacteria A+C or bacteria B+C combinations was totally dependent on the cell density of bacteria C. Conclusions Biofilm biomass of pure-species cultures was totally species-dependent, and the biofilm biomass of four species was in the following order: bacteria C > D > A > B. Relation between biofilm biomasses and SMP or EPS was inconsistent.